Transfer technology vs. Transfer knowledge in architecture and construction with land (REVISTA NODO, 2019)
This article is a reflection on how to “transfer technology”, a concept that starts from the idea of “Research”. “Development” and “Innovation” (R + D + I), and which in this case is framed in the context of architecture with land and in the ways of intervening in the environment to contribute to the configuration of a knowledge society and identify the evolution and potential of techniques associated with said process. From that perspective, the origin of this concept is analyzed when building with non-industrialized materials and the way to perpetuate traditional knowledge related to the development of said construction methods. In this document two cases of Colombian experiences are presented and the first results of these transferred techniques are evaluated. In that sense, the fundamental purpose of this article is to present an analysis of the experiences of architecture and construction with land that arise from the ancestral wisdom of the peoples, as a manifestation of their culture and of that “knowhow” where the expression underlies particular of a place and its response to the needs of the socioenvironmental context. With these experiences, another way of approaching the transfer in the construction of a new “development model” is proposed, which has more horizontal democratic implications in order to contribute to equity and harmonious coexistence with the environment for the welfare of all beings that inhabit the planet.
Keywords: Construction with land; technology transfer; quincha or bahareque; covered with domocaña